Lake Baikal isotope records of Holocene Central Asian precipitation - Swann, George E.A.; Mackay, Anson W.; Vologina, Elena; Jones, Matthew D.; Panizzo, Virginia; Leng, Melanie J.; Sloane, Hilary J.; Snelling, Andrea M.; Sturm, Michael (Elsevier, 2018)
Climate models currently provide conflicting predictions of future climate change across Central Asia. With concern over the potential for a change in water availability to impact communities and ecosystems across the region, an understanding of historical trends in precipitation is required to aid model development and assess the vulnerability of the region to future changes in the hydroclimate. Here we present a record from Lake Baikal, located in the southern Siberian region of central Asia close to the Mongolian border, which demonstrates a relationship between the oxygen isotope composition of diatom silica (δ18Odiatom) and precipitation to the region over the 20th and 21st Century. From this, we suggest that annual rates of precipitation in recent times are at their lowest for the past 10,000 years and identify significant long-term variations in precipitation throughout the early to late Holocene interval. Based on comparisons to other regional records, these trends are suggested to reflect conditions across the wider Central Asian region around Lake Baikal and highlight the potential for further changes in precipitation with future climate change.